Exploring the psychological antecedents of private and public sphere behaviours to reduce household plastic consumption - Lea Marie Heidbreder; Josephine Tröger; Manfred Schmitt (Environment, Development and Sustainability, 2022)
In the last few years, plastic has become an issue of current interest as tremendous ecological effects from plastic littering have become visible. Taking the role of consumers into account, activities comprising purchasing decisions and political engagement are expected to help prevent plastic pollution. The goal of this study was to examine antecedents of three potential plastic reduction activities: purchasing, activism, and policy support. Based on well-established psychological models of pro-environmental behaviour (i.e. theory of planned behaviour, norm activation model), an online survey ( N 0.167em=0.167em648) was administered and analysed via structural equation modelling. Results revealed that personal norms were a relevant predictor of all three intentions. Whereas sufficiency orientation and collective efficacy predicted only activism intention and policy support intention, perceived behavioural control was the strongest predictor of purchasing intentions. Regarding behaviour, people with high activism intentions and sufficiency orientation were more likely to choose a plastic-free incentive instead of the conventional shopping voucher. This study highlights psychological antecedents of plastic reduction. An integrated model showed that rational cost–benefit considerations as well as morality serve as drivers of reducing plastic consumption. Implications for the promotion of plastic-free consumption are discussed.
Keywords: 330; Environmental psychology; Pro-environmental intentions; Plastic consumption; Sufficiency orientation; TPB